THE RELATIONSHIP BETWEEN THE DIFFERENT TYPES OF TERMS IMPLIED INTO CONTRACTS (PART II) - Tjakie Naudé (Obiter, 2023)
In the first part of this contribution, I showed that the different categories of implied terms of a contract flow into each other in three respects. This raises the question whether the present approach of our courts to implied terms is satisfactory, especially given that it results in a blurring of borders between tacit and ex lege terms.Two alternative approaches to the present understanding of the borderlines between different types of implied terms will be considered in this final part of this article, before conclusions are drawn.